The chemical and electrochemical stimuli viologen substituted phthalocyanine with tunable optical features1 - Ates, Ozge Dilara; Tunc, Guelenay; Senocak, Ahmet; Dedeoglu, Burcu; Ayhan, Mehmet Menaf; Gürek, Ayşe Gül (Tubitak Scientific & Technological Research Council Turkey, 2023)
In this study, viologen-tetrasubstituted Zn(II) phthalocyanines (PcV1 and PcV2) were designed and synthesized to achieve the tunable optical features via redox-active viologen groups. Several parameters relevant to the evaluation of the tunable optical features have been investigated: UV-Vis, cyclic voltammetry (CV), EPR, square wave voltammetry (SWV), and theoretical analyses. The results showed that upon reductions and oxidations of viologen groups either chemically or electrochemically, the optical features of PcV1 and PcV2 change drastically with switchable processes. These outcomes indicate that achieving control over optical features of large organic chromophores such as Pc with our rational design can be used for the design of new complex organic electronic materials.
Keywords: Phthalocyanine; charged phthalocyanines; viologen; Zincke reaction; computational analyses